(Study on Additional Effect of Butylated Hdroxy Toluene (BHT) on extraction Quality of crudel, Degummed, and Bleached Castor Oil) - Rizal Alamsyah; Mirna Isyanti; Peri - (Balai Besar Industri Agro, 2007)
The study of additional effect of butylated hydroxy toluene (BHT)on extraction quality of crude,degummed,and bleached castor oil has been conducted.This study was aimed at elaborating the effect of BHT addition on every castor oil processing step e.g crude oil extraction,oil degumming,and oil bleaching.Such results were compared to those without BHT addition.To know the quality reduction of these oil extraction some parameters were treated namely FFA level and peroxide value.The BHT concentrations applied were 0.1 and 0,2% and the effect of these addition were monitored during 4 hours with 1 hour testing interval.The result shows that FFA level and feroxide value on bleaching step were lower than those of crude oil extraction and degummuing process.However antioxidant of BHT addition was able to reduce FFA and peroxide value compared to those wihout BHT and these data is very beautiful to know earlier if the oil processed can be processed better further and to prevent unwanted product.